The electronic barrier height of silicon native oxides at different oxidation stages - Qin, H. L. (2013)
A systematic study on silicon native oxides grown in ambient air at room temperature is carried out using ballistic electron emission microscopy. The electronic barrier height of Au/native oxide was directly measured for native oxides at different oxidation stages. While the ballistic electron transmission decreases with increasing oxidation time, the electronic barrier height remains the same, even after oxidation for 1 week. After oxidation for 26 months, the oxide layer showed the bulk-like SiO2 barrier; however, some local areas still show the same barrier height as that of an Au/n-Si device. This demonstrates the non-uniformity of native oxide growth.